Exploring issues in caregivers and parent communication of sexual and reproductive health matters with adolescents in Ebonyi state, Nigeria - Chinyere Ojiugo Mbachu; Ifunanya Clara Agu; Irene Eze; Chibuike Agu; Uche Ezenwaka; Nkoli Ezumah; Obinna Onwujekwe (BMC, 2020)
Abstract Background Parent-child communication is an effective tool for fostering healthy sexual and reproductive behaviours among adolescents. However, the topic is underexplored in Nigeria. This study examines how parents and caregivers communicate sexual and reproductive health-related matters with adolescents aged 13-18 years in Nigeria. Method The study was undertaken in six communities in Ebonyi state, Nigeria using quantitative and qualitative research methods. Data were collected through, i) cluster randomized survey of 1057 adolescents aged 13-18 years, ii) twelve sex-disaggregated focus group discussions with adolescents aged 13 to 18 years, and iii) eight in-depth interviews with parents and caregivers. Univariate and bivariate analysis were performed for quantitative data, while qualitative data were analysed using thematic framework approach. Results Less than half (47.9%) of adolescents in the survey reported ever discussing sex-related matters with anyone. Three-quarters of those who had this discussion did so with a friend/peer and this had significant correlation with sex/gender (p = 0.04). Out of 1057 adolescents who participated in the survey only 4.5% had ever discussed sex-related matters with a parent and this correlated significantly with wealth index (p = 0.003). Findings from qualitative interviews show that sex-related discussions between parents and adolescents are sporadic, mostly triggered by unpleasant occurrences, and consist of, i) information on pubertal changes, ii) warnings against intersex relationships and premarital sex, iii) promotion of abstinence, and iv) warnings against teenage pregnancy and unsafe abortion. Some parents were of the opinion that sex-related matters should not be discussed with adolescents because it could be interpreted as tolerance for sexual promiscuity. Overall, parents expressed that their capacity to discuss sex-related matters with adolescents is limited by lack of knowledge, and restrictive religious and cultural norms about adolescent sexuality. Conclusion Communication between parents and adolescents on sexual health and reproductive-related matters rarely occurs. However, when it does, it mostly consists of strict warnings that may not protect adolescents from making unhealthy sexual and reproductive health choices. Interventions to improve parent-adolescent communication of sexual and reproductive health (SRH) should aim at improving parents' capacity to communicate sexual and reproductive health matters, and deconstructing sociocultural norms around adolescent sexuality.